A survey and stakeholder group prioritised key systematic review questions in airways disease - Emma J. Dennett; Elizabeth M. Stovold; Rebecca Fortescue (Elsevier, 2022)
Objective: Priority setting is important for healthcare research. The Cochrane Airways Group wanted to prioritise topics for systematic reviews across all chronic respiratory diseases with limited resources and according to latest Cochrane policy.The objective was to prioritise 10 reviews of importance to the public (patients, carers, healthcare professionals and researchers) from a patient survey. Study design and setting: We convened a stakeholder group of patients, carers, healthcare professionals and representatives from charities. We conducted an online survey to collect uncertainties about the treatment and management of respiratory disease from the public. Uncertainties were ranked by the stakeholder group, and scoping searches refined the uncertainties into systematic review questions. Results: We received 147 survey responses. We removed duplicates and blank responses and asked the stakeholder group to rank 100 uncertainties. The first round of voting produced a list of 29 topics and the second round resulted in 12 uncertainties. These uncertainties were scoped with literature searches and teased out further into systematic review topics. We identified 3 Cochrane reviews to update, 8 new review topics, and 3 evidence gaps. Conclusion: We successfully convened a stakeholder group and prioritised a list of uncertainties in the treatment and management of airways diseases that had been identified by patients and the public.